Limiting Global Warming to Well Below 2 °C: Energy System Modelling and Policy Development (Lecture Notes in Energy, 2018)
This book presents the energy system roadmaps necessary to limit global temperature increase to below 2°C, in order to avoid the catastrophic impacts of climate change. It provides a unique perspective on and critical understanding of the feasibility of a well-below-2°C world by exploring energy system pathways, technology innovations, behaviour change and the macro-economic impacts of achieving carbon neutrality by mid-century. The transformative changes in the energy transition are explored using energy systems models and scenario analyses that are applied to various cities, countries and at a global scale to offer scientific evidence to underpin complex policy decisions relating to climate change mitigation and interrelated issues like energy security and the energy-water nexus. It includes several chapters directly related to the Nationally Determined Contributions proposed in the context of the recent Paris Agreement on Climate Change. In summary, the book collates a range of concrete analyses at different scales from around the globe, revisiting the roles of countries, cities and local communities in pathways to significantly reduce greenhouse gas emissions and make a well-below-2°C world a reality. A valuable source of information for energy modellers in both the industry and public sectors, it provides a critical understanding of both the feasibility of roadmaps to achieve a well-below-2°C world, and the diversity and wide applications of energy systems models. Encompassing behaviour changes; technology innovations; macro-economic impacts; and other environmental challenges, such as water, it is also of interest to energy economists and engineers, as well as economic modellers working in the field of climate change mitigation.